Etoposide‐induced cancer cell death: roles of mitochondrial VDAC1 and calpain, and resistance mechanisms - Aditya Karunanithi Nivedita; Varda Shoshan‐Barmatz (Molecular Oncology)
Etoposide is an inhibitor of DNA topoisomerase II, an enzyme essential for DNA transcription, replication, and chromosome segregation. It is well accepted that etoposide triggers cell death due to DNA damage. Our results indicate that multiple molecular mechanisms contribute to etoposide‐induced apoptosis, including the overexpression of the mitochondrial voltage‐dependent anion channel 1 (VDAC1) and its oligomerization, forming a mega‐channel that releases pro‐apoptotic proteins, thereby activating apoptosis. Etoposide induces C‐terminal truncation of VDAC1 (VDAC1‐ΔC) via the proteolytic actions of calpain‐1 and asparagine endopeptidase (AEP). A calpain‐specific inhibitor effectively prevented etoposide‐induced VDAC1‐ΔC formation, apoptosis, and the nuclear translocation of apoptosis‐inducing factor (AIF). Additionally, etoposide upregulates the expression levels of apoptosis regulators (p53, Bax, p21, AIF) and of the proteases calpain and AEP. Etoposide‐induced apoptosis and VDAC1 truncation are cell‐type dependent and associated with calpain levels and activity. Etoposide‐induced VDAC1‐ΔC formation and apoptosis are tightly linked: as both display similar patterns of concentration‐ and time‐dependence, both are inhibited by calpain and AEP inhibitors, as well as the VDAC1 oligomerization inhibitor VBIT‐4, and are dependent on intracellular Ca2+. These findings highlight the complexity of etoposide's actions in different cellular contexts, suggest possible mechanisms of resistance, offer potential biomarkers for guiding etoposide treatment in cancer patients, and propose targeting VDAC1 and calpain as promising therapeutic strategies in cancer therapy.